Analisis Faktor yang Berhubungan dengan Perilaku Gaya Hidup Sehat pada Remaja Kecanduan Game Online - Asiyami Ranistiya Widyaningrum; Syamsulhuda Budi Musthofa; Farid Agushybana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study analyzes factors related to healthy lifestyle behavior in teenagers addicted to online games. The method used is a quantitative approach with a cross-sectional survey design. The research results show that the dominant factors related to healthy lifestyle behavior in adolescents are gender, perceived barriers, perceived severity, friend support, teacher support, self-efficacy, promotion, and education. The variable with the largest Odds Ratio is the promotion variable with OR= 2.477 (95% CI: 1.392-4.405). In conclusion, promotion and education variables are the most dominant factors related to healthy lifestyle behavior in adolescents. Keywords: Factors, Online Game Addiction, Healthy Lifestyle Behavior, Teenagers